The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1158/2326-6066.cir-19-0703
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Immunomodulatory Capacity of Oncolytic Vaccinia Virus to Enhance the Immune Response to Breast Cancer

Abstract: Vaccinia virus (VACV) is a double-stranded DNA virus that devotes a large portion of its 200 kbp genome to suppressing and manipulating the immune response of its host. Here, we investigated how targeted removal of immunomodulatory genes from the VACV genome impacted immune cells in the tumor microenvironment with the intention of improving the therapeutic efficacy of VACV in breast cancer. We performed a head-to-head comparison of six mutant oncolytic VACVs, each harboring deletions in genes that modulate dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…These mice exhibit defective B and T lymphocytes, but normal NK cells, macrophage, and granulocytes. The mice were housed in BSL-2 containment and in conditions as detailed in Umer et al [30]. At day 0 the mice were anesthetized and 5 μl of PBS or viral inoculum was applied with a 10 μL pipette tip to a 1 cm scarification zone near the base of the tail.…”
Section: Animal Carementioning
confidence: 99%
“…These mice exhibit defective B and T lymphocytes, but normal NK cells, macrophage, and granulocytes. The mice were housed in BSL-2 containment and in conditions as detailed in Umer et al [30]. At day 0 the mice were anesthetized and 5 μl of PBS or viral inoculum was applied with a 10 μL pipette tip to a 1 cm scarification zone near the base of the tail.…”
Section: Animal Carementioning
confidence: 99%
“… 230 Since the disease eradication in the late 1970s, even though national vaccination programs ended, continuous research on vaccinia virus has produced numerous strains with improved safety profiles, some of them with oncolytic activity. 231 Recently initiated trials are evaluating five oncolytic strains of vaccinia virus either as single agents or in combination with ICIs ( Table 2 ). The Phase I NCT03954067 aims to evaluate the safety and tolerability of ASP9801 (which expresses IL7 and IL12) as a single agent and determine the RP2D in (sub)cutaneous and visceral tumors.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…In this study the virus was found to induce a mild anti-tumor response, however, the response was increased when the virus was combined with PD-1 and CTLA-4 antibodies. Another study examining the oncolytic activity of VACV mutants in BrCa was recently published by Umer et al [58]. In this study, the authors used six mutants of the Western Reserve (WR) strain of VACV each deleted in one or more immunomodulatory genes.…”
Section: Replicating Viruses For Breast Cancer Therapymentioning
confidence: 99%